Market study on the use of biomass for burning in the State of São Paulo, Brazil (Research, Society and Development, 2020)
The use of biomass as a renewable source of energy is an important characteristic of the Brazilian energy matrix. The energetic use of agricultural and forest biomass is a way of reducing production costs, taking advantage of residues, and reducing the use of fossil fuels. The objective of this study was to analyze the biomass market in the State of São Paulo to define which materials have more suppliers in the region and which have favorable properties for burning. For this, information was collected on the location of suppliers and the energetic characterization of the biomasses analyzed was made: briquette, wood chips, sawdust, firewood and eucalyptus wood, pine chips, cane bagasse, charcoal and rice husks. Data on the number of suppliers were obtained, by mesoregions, from a biomass purchase and sale website. Regarding the quantity produced, demanded and energetic properties of the analyzed biomasses, the data were obtained in reports and scientific articles. The results showed that there are more suppliers of firewood, chips and eucalyptus forest in the state of São Paulo.  Regarding the supply, the materials that have the highest production in the state are sugarcane bagasse, eucalyptus forest and firewood. Regarding the demand of the analyzed biomass, it was observed that they are most commonly used for energy production in the industries of: in the pulp and paper, steel, rice processing, ceramics, furniture, food and beverages. The biomasses that presented favorable energetic properties for burning were: charcoal, eucalyptus wood, firewood, briquette and eucalyptus chip and pine chip. It is concluded that the materials that have greater availability of suppliers, high production and are favorable for burning are: the eucalyptus chip, the firewood and the standing eucalyptus forest.